International human rights - "Donnelly, Jack" (Oxford, 1993)
This is an excellent introduction to a complex subject, filled with facts and figures but more importantly filled with stimulating ideas. Donnelly shows that he has thought long and hard about human rights in international perspective. The annotated bibliography and discussion questions are extremely useful for further reading and thinking.
Keywords: Human rights